A novel method for monitoring the imbibition behavior of clay-rich shale. (November 2020) - Meng, Mianmo; Ge, Hongkui; Shen, Yinghao; Ren, Fei; Ji, Wenming
Abstract: To research the imbibition behavior of shale reservoirs, the imbibition experiments were conducted. However, clay-rich shale has small particle detachment during imbibition, which causes conventional imbibition method failure. A novel method was proposed to deal with this problem and the imbibition behavior of clay-rich shale was investigated. In conventional method, the apparent imbibed volume increases quickly at initial time and decreases sharply at late time because of particle detaching from sample. This phenomenon happened even though the samples were coated with epoxy resin, which indicated that the clay has strong swelling property. In novel method, both deionized water and different kinds of KCl solutions as well as epoxy resin were used. When deionized water was used, the apparent imbibed volume has a decreasing interval, which may be caused by bubble effect and osmotic effect. When both high KCl solution was used and sample was coated with epoxy resin, the decreasing interval disappeared. The ultimate apparent imbibed volume of higher KCl solution is lower than the lower KCl solution, which indicates that K+ restrains the clay swelling and reduces imbibed liquid. At last, the difference between apparent imbibed volume and corrected imbibed volume was discussed. The main contribution of this study is that a novel method was proposed for monitoring the imbibition behavior of clay-rich shale.